Udržitelný rozvoj kulturně-historické krajiny a ochrana historických památek v zalesněném prostředí - Mazáčková, Jana (Masaryk University Press, 2022)
Title in English: Sustainable development of historical landscape and heritage protection in forested areas The publication presents the basic characteristics of cultural and historical landscape, its values and its sustainable development. It attempts to explain how it has been created and how it is being transformed, and what factors significantly influence the degradation of historical monuments (anthropogenic relics) in the forest environment. This is a publication suitable for woodland owners, but also for members of the public, interested in archaeological monuments that stand out or, burrow down into the natural relief of the landscape.